Relapse of acute malnutrition and associated factors after discharge from nutrition stabilization centers among children in Eastern Ethiopia - Alyi, Mohammedjemal; Roba, Kedir Teji; Ketema, Indeshaw; Habte, Sisay; Goshu, Abel Tibebu; Mehadi, Ame; Baye, Yohannes; Ayele, Behailu Hawulte (Frontiers in Nutrition, 2023)
Background: Acute malnutrition is a major global health problem affecting over 49 million under-five children. In sub-Saharan Africa, children treated for SAM at an inpatient have a 10 to 40% case fatality rate and is associated with relapse of acute malnutrition after discharge from inpatient treatment programs. However, there is limited data on the rate of relapse of acute malnutrition in children after discharge from stabilization centers in Ethiopia. Hence, this study aimed to assess the magnitude and predictors of relapse of acute malnutrition among under-five children discharged from stabilization centers in Habro Woreda, Eastern Ethiopia. Methods: A retrospective cross-sectional study was conducted from December 15, 2020 to January 15, 2021. A simple random sampling method was used to select participants. All randomly selected under-five children discharged from stabilization centers between June 2019 and May 2020 were included. Data were collected using pretested structured questionnaires and standard anthropometric measurements and supported by chart review. The anthropometric measurements were used to determine acute malnutrition. Data were entered into Epi-Data version 3.1 and analyzed using STATA version 14.2. Binary logistic regression analysis was used to identify factors associated with the outcome variable. An odds ratio with 95% CI was used to estimate the strength of the association. The statistical significance was declared at a P-value < 0.05. Results: The magnitude of relapse of acute malnutrition after discharge from stabilization centers was 36.2%(95% CI: 29.6,42.6). Mid-upper arm circumference <110mm at admission (AOR=2.80; 95% CI: 1.05,7.92), absence of latrine (AOR=2.50, 95% CI: 1.09,5.65), no home-based visits (AOR=2.81, 95% CI: 1.15,7.22), no vitamin-A supplementation (AOR=3.40, 95% CI: 1.40,8.09), household food insecurity (AOR=4.51, 95% CI: 1.40,15.06), poor dietary diversity (AOR=3.10, 95% CI: 1.31,7.33), and poor wealth index (AOR=3.90, 95% CI: 1.23,12.43) were significantly associated with relapse of acute malnutrition. Conclusion: The study revealed a very high magnitude of relapse of acute malnutrition among under-five children. Programmers and stakeholders working on nutrition should design interventions that focus on improving identified factors. Moreover, healthcare workers should give due emphasis to continuous follow-up visits, especially during the first six months of discharge, to reduce relapse of acute malnutrition.